Ethylene Epoxidation Catalyzed by Ag Nanoparticles on Ag‐LSX Zeolites formed by Pressure‐ and Temperature‐Induced Auto‐Reduction. Issue 5 (12th January 2018) - Kim, Donghoon; Lee, Yongmoon; Kim, Yonghwi; Mingle, Kathleen; Lauterbach, Jochen; Blom, Douglas A.; Vogt, Thomas; Lee, Yongjae
Abstract: Ag + ‐Exchanged LSX (Ag‐LSX: Ag96 Al96 Si96 O384 ⋅ n H2 O), a large pore low silica analogue (Si/Al=1.0) of faujasite, was prepared and post‐synthetically modified using pressure and temperature in the presence of various pore‐penetrating fluids. Using high‐resolution synchrotron X‐ray powder and single crystal diffraction we derive structural models of the as‐prepared and post‐synthetically modified Ag‐LSX materials. In the as‐prepared Ag‐LSX model, we located 96 silver cations and 245 H2 O molecules distributed over seven and five distinctive sites, respectively. At 1.4(1) GPa pressure and 150 °C in ethanol the number of silver cations within the pores of Ag‐LSX is reduced by ca. 47.4 %, whereas the number of H2 O molecules is increased by ca. 40.8 %. The formation of zero‐valent silver nanoparticles deposited on Ag‐LSX crystallites depends on the fluid present during pressurization. Ag‐nanoparticle‐Ag‐zeolite hybrid materials are recovered after pressure release and shown to have different chemical reactivity when used as catalysts for ethylene epoxidation. Abstract : Using hydrostatic pressure allows the formation of Ag nanoparticles on Ag‐LSX crystallites at lower temperatures while maintaining the crystallinity of the zeolite framework and increasing the conversion rate during the epoxidation of ethylene.